Exploring shared and unique benefits of passive and active prenatal intervention protocols on maternal wellbeing and neonatal outcomes: a combined quali-quantitative approach - Arioli, Martina; Consales, Alessandra; Savoldi, Melissa; Mastroianni, Ilenia; Gianni, Maria Lorella; Colombo, Lorenzo; Giovannini, Niccolò; Sacchi, Chiara; Macchi Cassia, Viola (Frontiers in Psychology, 2025)
IntroductionIn the present study, the shared and distinct effects of two novel prenatal intervention protocols implemented during the last trimester of gestation on perinatal maternal wellbeing and perinatal outcomes were explored.MethodsA total of 250 pregnant women at 28 weeks gestation were randomly assigned to either a Passive relaxation-based Protocol or an Active Protocol involving active maternal engagement in various motor activities during music listening. Anxiety and depression symptoms and attachment to the foetus/infant were assessed through self-report questionnaires before (t0) and after (t1) the protocol, as well 1.5 months postpartum (t2). Qualitative data on participants’ emotional experiences while performing the activities were collected through weekly diaries, together with adherence to the intervention protocol and the amount of engagement with the prescribed activities.ResultsGroup-level analyses showed that both protocols were associated with improvements in anxiety symptoms and attachment to the foetus/infant that extended to the postpartum period, while a different picture emerged for depression symptoms. Analyses of the data collected through the diaries revealed a more nuanced picture, showing that, within each group, maternal wellbeing outcomes and/or emotional experiences during the protocol were modulated by participants’ adherence and engagement with the prescribed activities. No differences between the two intervention groups were found in terms of the perinatal outcomes considered, but the number of relaxation sessions positively predicted newborns’ gestational age.DiscussionThese findings offer valuable insights into the mechanisms underlying the effects of passive versus active prenatal interventions, and point to the importance of tailoring intervention strategies based on individual preferences and perinatal stage.